Identification of potent inhibitors of the sortilin-progranulin interaction. Issue 17 (1st September 2020) - Stachel, Shawn J.; Ginnetti, Anthony T.; Johnson, Scott A.; Cramer, Paige; Wang, Yi; Bukhtiyarova, Marina; Krosky, Daniel; Stump, Craig; Hurzy, Danielle M.; Schlegel, Kelly-Ann; Cooke, Andrew J.; Allen, Samantha; et al.
Graphical abstract: Abstract: High-throughput screening methods have been used to identify two novel series of inhibitors that disrupt progranulin binding to sortilin. Exploration of structure-activity relationships (SAR) resulted in compounds with sufficient potency and physicochemical properties to enable co-crystallization with sortilin. These co-crystal structures supported observed SAR trends and provided guidance for additional avenues for designing compounds with additional interactions within the binding site.